Theoretical review on maladaptive perfectionism’s cognitive profile - Chemisquy, Sonia (2018)
Perfectionism may be understood as the tendency to set high and irrational standards, to stringently self evaluate and to asses self-worth based on achievementor failure. The cognitive model proposes the identification of cognitive profiles comprised of: schemas, beliefs, cognitive distortions, automatic thoughts and coping. The aim of this work was to describe maladaptive perfectionist’s cognitive profile. A non-systematic scientific literature review was made and empiric evidence was found. Maladaptive perfectionist's cognitive profile was described as the presence of schemas belonging to the disconnection/reject domain; beliefs about one’s need to be perfect and beliefs about contingent self-worth; biased interpretation of perfection, attentional bias and dichotomous thinking; perfectionistic automatic thoughts that associate with general negative cognitions, which tend to be maintained through rumination and self-criticism; and an emotion-focused coping style which is unhelpful to neutralize stressful situations. This article brings accessible and updated information which can be, useful to recognize the maladaptive perfectionist’s profile, and to identify goals for preventionor treatment interventions.